2014
DOI: 10.3389/fpls.2014.00158
|View full text |Cite
|
Sign up to set email alerts
|

A PCR-based forward genetics screening, using expression domain-specific markers, identifies mutants in endosperm transfer cell development

Abstract: Mutant collections are an invaluable source of material on which forward genetic approaches allow the identification of genes affecting a wide variety of biological processes. However, some particular developmental stages and morphological structures may resist analysis due to their physical inaccessibility or to deleterious effects associated to their modification. Furthermore, lethal mutations acting early in development may escape detection. We have approached the characterization of 101 maize seed mutants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…Previous studies identified 34 genes that show cell type-specific expression during endosperm differentiation (Gómez et al, 2009;Li et al, 2014;Muñiz et al, 2014) (Figure 3A). Consistent with the morphological abnormalities observed in seeds of the hda101-1 mutant, our results from the RNA-seq analysis, performed using three biological replications, showed that 26 out of these 34 genes exhibited a statistically significant decrease of their transcript level in 4-DAP seeds of the hda101-1 mutant compared with B73 ( Figure 3A).…”
Section: Expression Of Transfer Cell-specific Marker Genes Is Alteredmentioning
confidence: 97%
See 1 more Smart Citation
“…Previous studies identified 34 genes that show cell type-specific expression during endosperm differentiation (Gómez et al, 2009;Li et al, 2014;Muñiz et al, 2014) (Figure 3A). Consistent with the morphological abnormalities observed in seeds of the hda101-1 mutant, our results from the RNA-seq analysis, performed using three biological replications, showed that 26 out of these 34 genes exhibited a statistically significant decrease of their transcript level in 4-DAP seeds of the hda101-1 mutant compared with B73 ( Figure 3A).…”
Section: Expression Of Transfer Cell-specific Marker Genes Is Alteredmentioning
confidence: 97%
“…BETL-specific genes are often expressed in a dynamic pattern during endosperm development, characterized by significant upregulation at 4 to 8 DAP, when rapid cell differentiation and dramatic reprogramming of the kernel transcriptome take place (Gómez et al, 2009;Li et al, 2014;Muñiz et al, 2014). We therefore used RT-qPCR to assess whether loss of HDA101 protein in early seed development affects the temporal expression pattern of six BETL-specific genes ( Figure 3D).…”
Section: Expression Of Transfer Cell-specific Marker Genes Is Alteredmentioning
confidence: 99%
“…Most of the identified proteins showing decreased glycosylation in mn 1 were involved in post-translational modification, protein turnover, chaperone function, carbohydrate metabolism and cell wall biosynthesis, suggesting links to endoplasmic reticulum stress and the unfolded protein response in the mutant due to compromised glycosylation levels. Muñiz et al ( 2014 ) describe establishment of a PCR-based forward genetic screen using expression domain-specific markers to identify new mutant lines showing altered TC development. Application of this forward genetics approach using genes known to be tissue or developmental-stage specific offers new tools to extend the use of maize as a model for TC research.…”
mentioning
confidence: 99%